LEGAL PROTECTION FOR COMMUNITIES AFFECTED BY TOFU FACTORY WASTE IN BANGUN SARI BARU VILLAGE, TANJUNG MORAWA DISTRICT FROM THE PERSPECTIVE OF MASLAHAH MURSALAH - Kurnia Fanny; Zaid Alfauza Marpaung (Journal Analytica Islamica, 2025)
Legal protection for communities affected by tofu factory waste is very important to ensure that the community has a healthy and safe environment and that tofu factories are responsible for managing their waste. This study aims to analyze the problem of environmental pollution caused by the operational activities of tofu factories in Bangun Sari Baru Village in the implementation of Law No. 32 of 2009 and Maslahah Mursalah. This study uses an empirical juridical method and a case study approach, data obtained through field observations and interviews are then analyzed qualitatively using deductive logic. The results of the study indicate that tofu factories in Bangun Sari Baru Village do not have environmental permits and discharge waste without prior processing, this causes pollution and public health problems.